The frequency of diastolic dysfunction in patients with sarcoidosis and it’s relationship with HLA DRB1* alleles - Ozyilmaz, Ezgi; Akilli, Rabia; Berk, Ilayda; Deniz, Ali; Goruroglu Ozturk, Ozlem; Baydar, Oya; Saygideger, Yasemin; Seydaoglu, Gulsah; Erken, Eren (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Impaired systolic function is common in sarcoidosis however the frequency of diastolic dysfunction (DD) and it’s possible genetic basis has not been fully elucidated yet. The aim of this study is to evaluate the frequency of left ventricular DD(LVDD) and right ventricular DD(RVDD) and it’s possible relationship between Human Leukocyte Antigen(HLA)-DRB1* alleles in patients with sarcoidosis. Methods: Seventy seven patients (51 females, mean age 41.1±8.2yrs) without known sarcoid related or any other structured heart disease and 77 healthy controls with a similar age and gender (38.7±7.8yrs,51 females) were included in the case control study. DD was diagnosed with echocardiography. RVDD was defined as early(E)/late(A) ratio2 on tricuspit valve. LVDD was defined as E/A ratio2 on mitral valve, with isovolumetric relaxation time(IVRT)>90 miliseconds(msn) or deceleration rate of early diastolic flow(Edec)>220msn respectively. All patients were HLAtyped with the Sequence Specific Oligonucleotide Probe(SSOP) method. Results: The frequencies of LVDDs and RVDDs were significantly higher in sarcoidosis patients than the controls (26.0% vs. 2.6% for LVDD; and 42.9% vs. 18.2% for RVDD)(p